Deproteinization effects of NaOCl on acid-etched dentin in clinically-relevant vs prolonged periods of application. A confocal and environmental scanning electron microscopy study - Sauro, Salvatore; Mannocci, Francesco; Tay, Franklin R; Pashley, David H; Cook, Richard; Carpenter, Guy H; Watson, Timothy F (Operative dentistry, 2009)
Complete removal of the collagen matrix with sodium hypochlorite (NaOCl) as an adjunctive step of restorative and adhesive dentistry is still a subject for debate. This study evaluated the efficacy of a 12 w/v% NaOCl solution for complete removal of exposed collagen matrices from acid-etched dentin surfaces within a maximum clinically possible period of 120 seconds and a longer period of application (10 minutes) using confocal reflection/immuno-fluorescence microscopy and ESEM. An extended period (45 minutes) of NaOCl application was also performed as a negative control. Unstained and immunohistochemically-stained collagen fibrils were imaged using a confocal laser-scanning microscope for the reflection/fluorescence experiment. Fully-hydrated specimens were also examined with an ESEM. Unetched dentin was devoid of exposed collagen fibrils. Conversely, confocal microscopy showed demineralized collagen after acid-etching, which appeared as a hydrogel-like layer during ESEM examination. The application of NaOCl for two minutes left remnants of dentin collagen on intertubular and intratubular surfaces. The ESEM examination confirmed the presence of remnants of a hydrogel-like layer. After 10 minutes of NaOCl application, residual collagen reflection and immuno-fluorescence signals were detected around dentinal tubules, appearing as spike-like projections during the ESEM investigation. Complete dissolution of the collagen presence was achieved after 45 minutes of NaOCl treatment. Complete deproteinization of acid-etched dentin is unachievable in a maximum clinically possible period of 120 seconds.